2020
DOI: 10.1088/1742-6596/1521/3/032014
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of blended learning to improve pre-service teacher TPaCK in developing multimedia learning mathematics at elementary school

Abstract: This study aims to determine the effectiveness of blended learning towards the improvement of pre-service teacher TPaCK (Technological Pedagogical Content Knowledge) in developing multimedia learning mathematics in elementary schools. The type of this research is a quasi-experimental design. The research method used is a non-equivalent control group design. The population of this study was the 6th-semester students of the 2018/2019 academic year of the PGSD UAD study program of 315 students grouped in 7 classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
0
15
0
4
Order By: Relevance
“…The content analysis study of this article also revealed that there were several studies with the same research design but with different data collection techniques. This condition is seen in several studies with quasi-experimental designs, researchers only use test instruments (Lestari et al, 2020) then other researchers not only use tests but also questionnaires (Sintawati & Abdurrahman, 2020). Furthermore, several studies with survey research designs have researchers who use a collection instrument in the form of a questionnaire (Wulansari et al, 2020;Destiani & Purnawarman, 2020;Yanuarto et al, 2020) and some also use a collection instrument in the form of a test (Septiandari et al, 2020) Referring to the data collection instrument used, this study revealed that there were several articles that did not provide information regarding the validity of the instrument used.…”
Section: Subjects Selected During Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The content analysis study of this article also revealed that there were several studies with the same research design but with different data collection techniques. This condition is seen in several studies with quasi-experimental designs, researchers only use test instruments (Lestari et al, 2020) then other researchers not only use tests but also questionnaires (Sintawati & Abdurrahman, 2020). Furthermore, several studies with survey research designs have researchers who use a collection instrument in the form of a questionnaire (Wulansari et al, 2020;Destiani & Purnawarman, 2020;Yanuarto et al, 2020) and some also use a collection instrument in the form of a test (Septiandari et al, 2020) Referring to the data collection instrument used, this study revealed that there were several articles that did not provide information regarding the validity of the instrument used.…”
Section: Subjects Selected During Researchmentioning
confidence: 99%
“…In Thohir et al, 2020), use descriptive statistics (Septiandari et al, 2020), use paired sample t-test (Sintawati & Abdurrahman, 2020), and use ANOVA (Wulansari et al, 2020). The controversy over the choice of data analysis in experimental design research has been discussed several times (Knapp & Schafer, 2009).…”
Section: Data Analysis Techniquementioning
confidence: 99%
“…Pembelajaran blended learning sangat efektif untuk meningkatkan kemampuan TPACK calon guru SD (M. Sintawati & Abdurrahman, 2020). Pengetahuan, keterampilan dan sikap guru terhadap penggunaan teknologi sangat berpengaruh dalam proses pembelajaran (Seufert et al, 2021).…”
Section: Ketiga Pengetahuan Tersebut Saling Berinteraksi Dan Beririsa...unclassified
“…This research data collection method uses data collection by making observations (Sintawati & Abdurrahman, 2020). To test the quantitative data in the form of the results of the questionnaire, then several tests were carried out.…”
Section: Data Analysis Techniquementioning
confidence: 99%